Maktaba Library of the Year Awards: Looking back, looking forward - Ouma, Cary, Francis (My University, 2022)
This book is a product of my experience with the Maktaba Awards in different capacities. When the idea of Maktaba Awards was mooted in the year 2009, I was the Assistant Secretary of KLA. I therefore got the opportunity to sit in the formative meetings where the key framework decisions were made. In the year 2011, our library at Kenya National Archives and Documentation Service (KNA&DS) entered the competition and one thing I am forever proud of is that we won the Best Library Award (BLA) of that year. Having been the Deputy Head of the Library at KNA&DS, the victory gave me a perfect experience of what it is to compete in Maktaba Awards. Later in the year, 2013 I was elected the Vice Chairman of KLA. This position propelled me into joining the Maktaba Awards Management Committee and the Jury of 2014. These two capacities brought me to the core of Maktaba Awards activities. My role in these capacities became so strategic that by the end of activities of Maktaba awards 2014, which also marked the end of the first phase of the programme, I was appointed by the chairman KLA to prepare a proposal for re-engineering of maktaba awards in the next phase. Consistent with the public sector planning cycles in Kenya, five years of Maktaba awards was adopted as one phase. In Kenya, all government strategic plans cover five years. I therefore prepared a proposal which was presented and adopted by the KLA Annual General Meeting of 2014. The proposal looked at the five years of maktaba and made analytical projections into the next phase by of course taking stock of the strengths, weaknesses and opportunities. That proposal formed the synopsis for this book. It comprised in two parts – the experience and the future of the award, thus looking back looking forward. In preparing the book, I was forced to do a broad based comparative reading between maktaba and other awards across the globe. It is out of this that my mind was awakened to the need for a book in the area of awards generally and library awards specifically. . In spite of very many awards projects and programmes in librarianship and other fields, there is very little if any publishing in the area. This is a naked literature gap which if filled will serve a significant utility. In regard to maktaba, a book of this nature will effectively deal with the information gap among stakeholders. Out of ignorance, librarians have continuously complained about some aspects of the awards particularly the judgment criteria. Most importantly, the book has given a critical analysis of all the major aspects of library awards. This will significantly inform the planning and decision making for the next phase of the awards by the concerned organs. The book is a must read for all the librarians who have interest in maktaba Awards. The principles can also be shared with all other professions who have interest in mounting excellence awards.
Keywords: awards; Library; Maktaba